ELLIPSE-BASED TEMPLATE MATCHING FOR CELL IDENTIFICATION IN FLUORESCENCE MICROSCOPE IMAGES - MKAYES, ABED ALRAHMAN (2016)
Automatic Cell detection in fluorescence microscopy (FM) images is an essential operation in automated cell analysis for diagnosis and treatment of oral cancer which includes the study of cell shapes. This should enable biologists to detect and count all the cells automatically in fluorescence images which provide high reliability and assist the clinician's work. In this work, a cell detection method in fluorescence microscope images in green channel obtained from Cancer Research Malaysia is proposed. This method is divided into two main stages, image enhancement, and cell detection. The aim of image enhancement is to remove noise and enhance cells boundary prior to cell detection operation.